Comparative analysis between synthetic mammography reconstructed from digital breast tomosynthesis and full-field digital mammography for breast cancer detection and visibility. (2020) - Murakami, Ryusuke; Uchiyama, Nachiko; Tani, Hitomi; Yoshida, Tamiko; Kumita, Shinichiro
Highlights: 2D synthetic mammography images from the DBT dataset do not require additional radiation exposure. We compare observer performance between 2DSM and FFDM for breast cancer detection and visibility. Diagnostic performances of 2DSM and FFDM images were comparable for detecting breast cancers. 2DSM may eliminate the need for additional FFDM during DBT-based imaging. Abstract: Purpose: To compare observer performance between synthetic mammography (2DSM) and full-field digital mammography (FFDM) for breast cancer detection and visibility. Method: A retrospective analysis was conducted on 136 histopathologically proven cases of breast cancer in patients who underwent FFDM and digital breast tomosynthesis (DBT). 2DSM images were reconstructed from DBT data, and 2DSM and FFDM images were reviewed and evaluated for mammographic features, probability of malignancy (BI-RADS classification), and lesion conspicuity. DBT images were not reviewed. Statistical differences in cancer detection rates between 2DSM and FFDM images were analyzed using the McNemar test, agreement on BI-RADS assessment between 2DSM and FFDM was assessed using Cohen's kappa test, and the Wilcoxon's signed rank test was used to compare visibility scores. Results: Mean cancer detection rates with 2DSM and FFDM images were 84.6 % and 87.8 %, respectively. In subgroup analyses, differences in breast density, tumor size, and presence of calcifications were not statistically significant. Agreement between 2DSM and FFDM images for BI-RADS classification was graded as good with Cohen's k-coefficient of 0.78 ± 0.05. Visibility scores in both modalities of images were similar for all lesions combined; however, 2DSM had significantly better visibility scores for calcified cancers (p < 0.01), and in dense breast tissue (p < 0.01). Conclusions: Diagnostic performances of 2DSM and FFDM images were comparable for detecting breast cancers, and it is possible that 2DSM may eliminate the need for additional FFDM during DBT-based imaging due to advances in image reconstruction methods.